The Effect of Stress Management Counseling on General Health and Coping Strategies for Women with Breast Cancer - masoumi SZ; Tohidi Sh; Jamshidi F; Farhadiyan M; Forouhari S; Shayan A (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Breast cancer is the most common cancer that endangers the women's mental health. Objectives: The purpose of this study is to evaluate the effectiveness of stress management consulting on coping strategies in women with breast cancer. Methods: This is a quasi-experimental, with pre- and post-test design and follows up with control and intervention groups. 104 women with breast cancer referring to MRI Center of Mahdieh in Hamadan-Iran in 2015 were divided randomly into two groups that the number of each group using permutation blocks was 52. The intervention group received the stress management counseling sessions through. Data collection tools were demographic questionnaire and general health questionnaire and the questionnaire of coping strategies of Lazarus & Folkman. For data analysis, the descriptive statistics and repeated measures analysis were used. Results: The results of this study showed that the intervention can improve the general health and its sub-scales in intervention group. After intervention, a significant difference in average scores of the general health in two groups was observed (P<0.000). Also, there was a remarkable difference in average scores of the coping strategies in two groups before and after intervention (P<0.000), the problem-focused coping strategies in intervention group through post-test and follow up steps increased but the emotion-focused coping strategies in intervention group decreased. Conclusion: The cognitive-behavioral group therapy of stress management can improve general health and increase coping strategies in patients with breast cancer, so this method can be used in oncology centers as the complementary therapy alongside the medical treatments.